Stability of Generalized Quartic Functional Equation in Random Normed Spaces
Aim of this paper is to investigate the Hyers-Ulam stability of generalized quartic functional equation align* ^n_i=1(-v_i+^n_j=1,i eq jv_j) &=(n-8)_1=i<j<k<l=n(v_i+v_j+v_k+v_l) onumber &-(n^2-12n+28)_1=i<j<k=n(v_i+v_j+v_k) &+(n^3-15n^2+60n-682)_1=i<j=n(v_i+v_j) onumber &+2_1=i<j=n(v_i-v_j)+^n_i=1(3v_i) &-(n^4-17n^3+86n^2-148n+558